Sodium‐Ion Batteries: Isostructural and Multivalent Anion Substitution toward Improved Phosphate Cathode Materials for Sodium‐Ion Batteries (Small 16/2020). Issue 16 (23rd April 2020) - Wang, Mei‐Yi; Guo, Jin‐Zhi; Wang, Zhi‐Wei; Gu, Zhen‐Yi; Nie, Xue‐Jiao; Yang, Xu; Wu, Xing‐Long
Abstract : In article number 1907645, Xing‐Long Wu and co‐workers propose and develop an advanced strategy (isostructural and multivalent anion substitution strategy) to significantly enhance the electrochemical properties of Na‐super‐ionic conductor‐type phosphate cathode (from Na3 V2 (PO4 )3 to Na3.1 V2 (PO4 )2.9 (SiO4 )0.1 ) for sodium‐ion batteries. In addition, theoretical calculation and experimental analyses reveal the anionic manipulation and improvement mechanism.